Graphene Inks as Versatile Templates for Printing Tiled Metal Oxide Crystalline Films. Issue 4 (7th December 2017) - Liu, Muchun; Chen, Po‐Yen; Hurt, Robert H.
Abstract: There is great interest in exploiting van der Waals gaps in layered materials as confinement reaction vessels to template the synthesis of new nanosheet structures. The gallery spaces in multilayer graphene oxide, for example, can intercalate hydrated metal ions that assemble into metal oxide films during thermal oxidation of the sacrificial graphene template. This approach offers limited control of structure, however, and does not typically lead to 2D atomic‐scale growth of anisotropic platelet crystals, but rather arrays of simple particles directionally sintered into porous sheets. Here, a new graphene‐directed assembly route is demonstrated that yields fully dense, space‐filling films of tiled metal oxide platelet crystals with tessellated structures. The method relies on colloidal engineering to produce a printable "metallized graphene ink" with accurate control of metal loading, grain size/porosity, composition, and micro/nanomorphologies, and is capable of achieving higher metal–carbon ratio than is possible by intercalation methods. These tiled structures are sufficiently robust to create free standing papers, complex microtextured films, 3D shapes, and metal oxide replicas of natural biotextures. Abstract : Uniform stacking of hybrid metal cation graphene oxide nanosheets provides a 2D assembly route that yields fully dense, space‐filling films of tiled metal oxide platelet crystals with tessellated structures. These tiled structures are sufficiently robust to create free standing papers, complex microtextured films, 3D shapes, and metal oxide replicas of natural biotextures.